Pengenalan Arsitektur Berkelanjutan dan Penerapan Material Ramah Lingkungan bagi Siswa SMK 3 Boyolangu - Diyah Ayu Saputri; Mochamad Rizqi Junianto; Samas Wirya Dinata (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
This community service activity aimed to introduce the concepts of sustainable architecture and eco-friendly materials to students at SMKN 3 Boyolangu, Tulungagung Regency specifically those in grades X and XI of the DPIB (Design, Modeling, and Building Information) and TKP (Construction and Property Engineering) departments. The initiative addressed the lack of integration of sustainable architecture concepts into the vocational high school (SMK) curriculum, a gap that creates a disparity between graduate competencies and the demands of the green construction industry. The activity employed a participatory approach combining the presentation of basic green building concepts, demonstrations of eco-friendly materials, and Focus Group Discussions (FGDs) to identify student needs. Program effectiveness was evaluated through pre- and post-tests, questionnaires, FGDs, and field observations. Evaluation results showed that students' understanding of basic sustainable architecture and green building concepts rose from 30% to 95% (+65%); understanding and the ability to apply eco-friendly materials increased from 50% to 95% (+45%); and environmental awareness and concern improved from 60% to 95% (+35%). Findings from the FGDs and observations further corroborated the qualitative increase in students' environmental awareness. This activity makes an initial contribution toward preparing vocational graduates for the sustainable construction industry while strengthening the partnership between the Architecture Study Program at Universitas Bhinneka PGRI Tulungagung and SMKN 3 Boyolangu in developing environmentally conscious vocational education. In conclusion, raising awareness about sustainable architecture effectively improved students' understanding and readiness in a measurable way; however, follow-up activities involving practical design mentoring are needed to reinforce the application of these concepts in actual projects.